Breeding report of a new mid-maturing sand pear cultivar Zheli No. 6 - DAI Meisong; CAI Danying; WANG Yuezhi; WEI Chunyan; SHI Zebin (Guoshu xuebao, 2025)
Zheli No. 6 (original code: A14, also known as Wancui) is a mid-maturing, table pear (Pyrus pyrifolia L.) variety with excellent internal quality. The cultivar was selected from Cuiguan seedling population. The paternal parent was identified as Qingxiang through SNP molecular markers. The Cuiguan pear seeds were obtained at the base of Hangzhou Binjiang Fruit Industry Co., Ltd. in Binjiang District, Hangzhou in 2001. Over 300 seedlings were raised in 2002, and these seedlings were planted in the pear breeding nursery in 2003, resulting in 71 seedling trees. Some of the individual plants in this group began to bear fruit in 2006. One of them with the nursery code A14 stood out for its large fruit size and excellent internal quality. It was then identified as a superior strain and multi-sites field trials were initiated in the autumn. Consecutive observations were made on the trial trees in the area at the Haining Yangdu base of the Zhejiang Academy of Agricultural Sciences from 2011 to 2018, and the fruiting and cultivation characteristics of the strain were found stable. Consequently, it was confirmed as the final selected superior strain. After years of continuous observation, the strain was named Zheli No. 6 and submitted for China Plant Variety Protection application in January 2017. It was passed the on- site inspection in October 2017 and granted authorization in April 2019 (Certificate number: CNA20170034.7). It was also approved by the Fujian Provincial Forest Tree Variety Committee (Certificate number: Fujian S-SV-PP-018-2022) in 2022. The tree was vigorous and semi-spreading, and the trunk bark of mature tree was smooth. The 1-year-old branches weres straight, with an average internode length of 5.1 cm. The main color of the sunny side of the branches was reddish-brown. The young leaves were light red, and the mature leaves were ovate. The flowers were white without red blush, the petals were entirely white and ovate, the stigma was the same height as the anthers, and the anthers were purple-red. The fruit was nearly round with a raised calyx end, and with a green peel that featured rust spots. The flesh was white, fine, crispy, and juicy. The average single fruit weight was 355 g, and the maximum single fruit weight was 750 g. The fruit shape index was 0.93. The fruit quality was excellent, with a soluble solid content of 14%. The average flesh hardness was 3.1 kg·cm-2. The fruit matured in the mid-August in the Haining area of Zhejiang Jiaxing and in the end of July in the Jianning area of Fujian, approximately 20 days later than that of the local Cuiguan cultivar. It was a self-incompatible cultivar with S3S7 genotype. Huanghua (S1S2), Cuiguan (S3S5) and Cuiyu (S3S4) were recommended as pollinater varieties. The spacing could be 4 m × (2-3) m in plain areas, and 3 m × 2 m in hilly areas.